2015
DOI: 10.1016/j.sbspro.2015.01.462
|View full text |Cite
|
Sign up to set email alerts
|

Ninth Grade Student’ Self-assessment in Science: A Rasch Analysis Approach

Abstract: Based on the competency indicators of the nine-year compulsory curriculum in Taiwan, this study constructed a self-assessment scale suitable for use by junior high school students to evaluate their comprehension of sciencerelated concepts. Using random strata sampling this study surveyed ninth grade students in Taiwan in 2012. A total of 1,326 questionnaires were distributed and 1,005 valid questionnaires were recovered. The Rasch model was employed to study the self-assessment results and analyze difficulties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…al, 2015;Park et al 2017;Lee et al, 2011). The concept of the Rasch model is not just a technique that shows the level of difficulty and feasibility of the question assessment instrument, but it is also able to show the pattern of student answers in responding to the problem (Sumintono, 2018;Chiang, 2015). In other words, the use of the Rasch model confirms that each student has the same opportunity to answer questions correctly, not just about items (Park et al 2017;Chan et al, 2014).…”
Section: Indonesian Journal On Learning and Advanced Educationmentioning
confidence: 99%
“…al, 2015;Park et al 2017;Lee et al, 2011). The concept of the Rasch model is not just a technique that shows the level of difficulty and feasibility of the question assessment instrument, but it is also able to show the pattern of student answers in responding to the problem (Sumintono, 2018;Chiang, 2015). In other words, the use of the Rasch model confirms that each student has the same opportunity to answer questions correctly, not just about items (Park et al 2017;Chan et al, 2014).…”
Section: Indonesian Journal On Learning and Advanced Educationmentioning
confidence: 99%
“…Most of the issues of concern to math teachers relate mainly to questions such as class size, student heterogeneity, the value of the thinking stages in the solution processes, and reliability and validity of math evaluation. Studies have also revealed that many teachers feel that they lack the knowledge of apply alternatives to the quantitative-traditional assessment (Abali et al, 2014;Al-Nouh et al, 2014;Biton & Halfon, in print;Black & Wiliam, 2012;Chiang, 2015;Darmody et al, 2020;Davison & Leung, 2009;Galustyan, 2017;Savickiene, 2011;Veldhuis & van den Heuvel-Panhuizen, 2020;Zhao et al, 2018). To date, the foci of mathematics teachers' considerations have not yet been thoroughly examined from the many different aspects of assessment which help them as they approach choosing and evaluating their students' achievements, knowledge and skills acquired in learning.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative assessment methods are correlated with higher achievement levels, learning motivation and diligence, and students' perception of student efficacy (Sahin & Abali Ozturk, 2014). Hence, traditional evaluation methods should be used with alternative ones (Chiang, 2015;Veldhuis & van den Heuvel-Panhuizen, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…To satisfy these requirements, we drew on the Rasch model while constructing and evaluating a new instrument, the test of basic Mechanics Conceptual Understanding (bMCU). There is a growing number of studies on the evaluation of test instruments in the science education literature that are based on Rasch modeling (e.g., Cheng and Oon, 2016; Chiang, 2015; Kuo, Wu, Jen, and Hsu, 2015).…”
Section: Introductionmentioning
confidence: 99%